Republic of Poland : Technical Assistance Report-Progress Report on Budget System Reform-Developing a Standard Chart of Accounts and a Medium-term Budget Framework. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
The Polish government is making good progress with implementing the ambitious Budget System Reforms (BSR) program, first approved by the Council of Ministers (CoM) in 2016. The government demonstrates a high level of commitment to these reforms and is making significant progress in implementing the recommendations of earlier FAD missions with the support of the resident advisor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet